Passive terahertz image processing (I) - Tang, Jia Wei (Nanyang Technological University, 2023)
Terrorism originated from the late 18th century and gained world-wide attention in 1970s during the Israeli-Palestinian conflict. Since then, countries have stepped up their efforts in security systems to safeguard the interest of their country. The project hopes to achieve both its scientific and social goals. The scientific goals highlight the process of research and invention of an intelligent machine learning model capable of detecting contraband goods via the use of imaging technology, passive terahertz. The social goals the project hope to achieve would be achieved through the invention of the product mentioned in the project where the occurrence of terrorism would be reduced and ideally prevented.